Patterns of cortical thickness associated with impulse control disorders in Parkinson's disease. Issue 5 (4th February 2015) - Biundo, Roberta; Weis, Luca; Facchini, Silvia; Formento‐Dojot, Patrizia; Vallelunga, Annamaria; Pilleri, Manuela; Weintraub, Daniel; Antonini, Angelo
Abstract Previous functional neuroimaging studies in Parkinson's disease (PD) patients with impulse control disorders (ICDs) demonstrated dysfunction of the reward network, although the extent of anatomical changes is unclear. The aim of this study was to measure brain cortical thickness and subcortical volumes, and to assess their relationship with presence and severity of symptoms, in PD patients with and without ICDs. We studied 110 PD patients (N = 58 with ICDs) and 33 healthy controls (all negative for ICDs) who underwent an extensive neurological, neuropsychological, and behavioral assessment as well as structural 1.5 Tesla magnetic resonance imaging (MRI). Between‐group differences in brain cortical thickness and subcortical volumes, assessed with the FreeSurfer 5.1 tool, were analyzed. In patients with ICDs, we found significant cortical thinning in fronto‐striatal circuitry, specifically in the right superior orbitofrontal, left rostral middle frontal, bilateral caudal middle frontal region, and corpus callosum, as well as volume reduction in the right accumbens and increase in the left amygdala. Finally, we observed a positive association relationship between severity of impulsive symptoms and left rostral middle frontal, inferior parietal, and supramarginal areas. These results support the involvement of both reward and response inhibition networks in PD patients with ICDs. Moreover, their severity is associated with alterations in brain regions linked with reward and top‐down control networks. Increased understanding of the mechanisms underlying impulsive and compulsive behaviors might help improve therapeutic strategies for these important disorders. © 2015 International Parkinson and Movement Disorder Society